Role Of Processed And Natural Cotton On Aedes Aegypti Egg Hatching - Wagner, Ricky; Menghwar, Sepna; Drame, Papa; Montenegro-Cadena, Lidia; Londono-Renteria, Berlin (My University, 2018)
Ae. aegypti is an invasive species and playing a crucial role in disseminating the infectious diseases like dengue and Zika fever. This mosquito, prefers to live in areas close to humans where blood is easily accessible (Powell, et al. 2013). Female Ae. aegypti mosquitoes use the blood meal to obtain the nutrients necessary for reproduction to complete their life cycle. After a female takes the blood meal into her midgut, the blood proteins are enzymatically digested into amino acids, which are then released into the hemolymph nutrients (Pacey & O'Donnell, 2014). While working on mosquitoes in insectary, we observed that certain cotton types have effect on oogenesis as the obtained eggs were not hatching and if hatched it took longer time than usual. This leads us to key hypothesis, that either cotton fibers are blocking certain essential nutrients or there could be some chemicals in processed cotton that are affecting egg development. The current research can be a big step towards the suppression of mosquitoes. Considering the current situation in endemic areas we need to come up with new and effective tools.
Keywords: Fall 2018